Altered brain activities in mesocorticolimbic pathway in primary dysmenorrhea patients of long-term menstrual pain - Liu, Ni; Li, Yingqiu; Hong, Yueying; Huo, Jianwei; Chang, Tai; Wang, Haoyuan; Huang, Yiran; Li, Wenxun; Zhang, Yanan (Frontiers in Neuroscience, 2023)
Background Patients with primary dysmenorrhea (PDM) often present with abnormalities other than dysmenorrhea including co-occurrence with other chronic pain conditions and central sensitization. Changes in brain activity in PDM have been demonstrated; however, the results are not consistent. Herein, this study probed into altered intraregional and interregional brain activity in patients with PDM and expounded more findings. Methods A total of 33 patients with PDM and 36 healthy controls (HCs) were recruited and underwent a resting-state functional magnetic resonance imaging scan. Regional homogeneity (ReHo) and mean amplitude of low-frequency fluctuation (mALFF) analysis were applied to compare the difference in intraregional brain activity between the two groups, and the regions with ReHo and mALFF group differences were used as seeds for functional connectivity (FC) analysis to explore the difference of interregional activity. Pearson's correlation analysis was conducted between rs-fMRI data and clinical symptoms in patients with PDM. Results Compared with HCs, patients with PDM showed altered intraregional activity in a series of brain regions, including the hippocampus, the temporal pole superior temporal gyrus, the nucleus accumbens, the pregenual anterior cingulate cortex, the cerebellum_8, the middle temporal gyrus, the inferior temporal gyrus, the rolandic operculum, the postcentral gyrus and the middle frontal gyrus (MFG), and altered interregional FC mainly between regions of the mesocorticolimbic pathway and regions associated with sensation and movement. The anxiety symptoms are correlated with the intraregional activity of the right temporal pole superior temporal gyrus and FC between MFG and superior frontal gyrus. Conclusion Our study showed a more comprehensive method to explore changes in brain activity in PDM. We found that the mesocorticolimbic pathway might play a key role in the chronic transformation of pain in PDM. We, therefore, speculate that the modulation of the mesocorticolimbic pathway may be a potential novel therapeutic mechanism for PDM.